The efficacy of negative pressure wound therapy on chemotherapeutic extravasation ulcers: An experimental study - Evren Isci; Halil I. Canter; Mehmet Dadaci; Pergin Atilla; Ayse N. Cakar; Abdullah Kecik (Indian Journal of Plastic Surgery)
Context: The extravasation of the chemotherapeutic agents is not an unusual phenomenon. Necrosis of the skin and underlying structures has been reported, depending on the cytotoxicity of the extravasating drug. Despite the presence of some antidotes, such wounds tend to enlarge with time and are likely to resist the treatment. Aims: The objective of this study was to investigate the efficacy of negative pressure wound therapy (NPWT) on extravasation ulcers. Settings and Design: Animals were separated into two groups; conventional dressing group and NPWT group. Materials and Methods: Extravasation necrosis was established by intradermal doxorubicin injection. Following the debridement of the necrotic areas, one group of animals was treated with the conventional dressing while NPWT was applied to the other group. The wound areas were measured, and then biopsies were taken on the 3rd, 7th and 14th days after the debridement. Statistical Analysis Used: SPSS 11.5 for Windows was used. Two-way ANOVA test was used to compare wound areas between groups. Willcoxon sign test with Bonferroni correction was used to compare histological scores between groups. Chi-square test with Bonferroni correction was used to compare histological scores within the group between the days. Results: There is no significant difference in terms of inflammatory cell count, neovascularisation, granulation tissue formation between the groups. Contrary to these results wound areas at the end of the treatment were smaller in the NPWT group compared with the dressing group. Conclusion: There is the superiority of NPWT over conventional dressing in chemotherapeutic extravasation wounds as well as the wound area is concerned, but it is not proven histologically.